Driade space: an agent based simulation model for the analysis of the firm demography and the localization patterns in urban areas - Carlos Mu\~noz; Federico Pablo (European Regional Science Association (ERSA), 2002)
An agent based model of firm mobility is presented in which diverse types of firms decide their geographical localization in function of some spatial variables. Although as much the regional economy as the geography have studied in depth the rules of localization of the companies, many of the complex behaviors that are observed in the reality are still, in great measure, unexplained. The simulation based on agents constitutes a new approach to the problem, allowing to integrate in the models of economy regional aspects of great relevance that, for its high complexity, could not be included in the analysis more than in qualitative terms. In the Driade Space model the demography of firms is considered in a wide sense: number of firms, entries and exits, distribution of sizes as well as the spatial density of firms. The entry of new companies in each period depends on the evolution of the market. The number of these is function of the profitability observed in the sector in the previous period and the height of the entry barriers. The companies are rational and they act on the variables within their reach in function of their objectives and of the limited information they have on the evolution of the market and the behavior of their competitors. This way, the companies in the moment of their entrance decide the localization they expect that will be more profitable considering their own characteristics while in the successive periods they decide on their investments and their production. The costs of the companies are not fixed; they depend not only on the production level and on the price of the used productive factors but also on the price of the land. The derived economies of the initial decision of localization are also considered. The characteristics of the territory where the firms are located are not static but rather evolve depending on the applied policies, demographic variables and the localization of the companies. Although the exits of the companies depend mainly on their profitability, they are also affected by random aspects. When the companies exit the market they leave a free space that can be covered by other companies favoring this way new entries. The model presented allows showing the endogenous rules of firm localization as well as the effects in the medium and the long term of the public policies.
Keywords: 330